PENANGANAN PELAKSANAAN BONGKAR MUAT VCM (C2H3CL) DI KAPAL MT. GAS KALIMANTAN LPG CARRIER TYPE-C - Eko Murdiyanto; Ilham Pratama; Agus Hadi Purwantomo (Dinamika Bahari, 2018)
In the process of loading and discharging cargo, especially VCM cargo should becarried out in the best. It requires careful preparation good from the ship and shore.Basically handling barriers aims to overcome the problem that can be solved well whenloading and unloading process. The problem that the authors take here is How to handlingloading and discharging of the vessel MT. Gas Kalimantan? How preparation when loadingand unloading in the MT. Gas Kalimantan? Platform used here is the handling cargo is aknowledge of the loading and unloading of ship and upwards so that materialize the fiveprinciples of good loading unloading is a load or unload shipping activities of a charge anddock. In this scribd using qualitative descriptive study data download data throughobservation and interviews.